2004
DOI: 10.1194/jlr.m300373-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomevalonate kinase is a cytosolic protein in humans

Abstract: In the past decade, a predominant peroxisomal localization has been reported for several enzymes functioning in the presqualene segment of the cholesterol/isoprenoid biosynthesis pathway. More recently, however, conflicting results have been reported raising doubts about the postulated role of peroxisomes in isoprenoid biosynthesis, at least in humans. In this study, we have determined the subcellular localization of human phosphomevalonate kinase using a variety of biochemical and microscopic techniques, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The punctate Xuorescence did not reXect a mitochondrial localization, as determined by co-localization studies using the mitochondrial marker cytochrome c (data not shown); a lysosomal localization, as determined by co-localization studies using the lysosome markers Limp-1 and Lamp-2 (data not shown); or endosomal localization, as determined by co-localization studies using antibodies to early endosome antigen 1 (EEA1) and Rab5 (data not shown). Interestingly, these observations are similar to those published by Hogenboom et al (2004b), who observed a punctate pattern that did not co-localize with the punctate pattern of the peroxisomal catalase or the PMP ALDP (adrenoleukodystrophy protein). Thus, they reached the conclusion that this enzyme was not localized to peroxisomes.…”
Section: Phosphomevalonate Kinasesupporting
confidence: 91%
“…The punctate Xuorescence did not reXect a mitochondrial localization, as determined by co-localization studies using the mitochondrial marker cytochrome c (data not shown); a lysosomal localization, as determined by co-localization studies using the lysosome markers Limp-1 and Lamp-2 (data not shown); or endosomal localization, as determined by co-localization studies using antibodies to early endosome antigen 1 (EEA1) and Rab5 (data not shown). Interestingly, these observations are similar to those published by Hogenboom et al (2004b), who observed a punctate pattern that did not co-localize with the punctate pattern of the peroxisomal catalase or the PMP ALDP (adrenoleukodystrophy protein). Thus, they reached the conclusion that this enzyme was not localized to peroxisomes.…”
Section: Phosphomevalonate Kinasesupporting
confidence: 91%
“…These results have been challenged by data supporting the possibility that the biosynthetic reactions leading to mammalian sterols (e.g. cholesterol) occur mostly in the cytosol (Hogenboom et al, 2004;Wanders and Waterham, 2006). Localization of the rate-limiting enzyme, HMGR, and the first committed enzyme of sterol biosynthesis, squalene synthase, to the ER are in general agreement.…”
mentioning
confidence: 61%
“…This enzyme was first believed to be localized in the cytosol of plants (24) and animals but later was described as mitochondrial (13) and plastidic (49). Moreover, it has been described that peroxisomes are the major site of the synthesis of FPPS from mevalonate in human cells (2), while other studies maintain a cytosolic location for the conversion of mevalonic acid to isopentenyl diphosphate (21,22). Digitonin permeabilization is a classical way to assess the subcellular localization of a protein.…”
Section: Resultsmentioning
confidence: 99%